OPTIMIZATION OF THE FOUR WHEEL PATROL OF SATSAMAPTA TO PREVENT THE CRIME OF CURRENCY IN THE JURISDICTION OF THE SRAGEN POLICE - DOLAS ZIMMI SAPUTRA NAINGGOLAN (Indonesian Journal of Police Studies, 2022)
Dolas Zimmi Saputra Nainggolan, No. Ak 18,098, dolas18098@gmail.com The background of writing this final project is the information that shows that in the jurisdiction of the Sragen Police, there is a high rate of motor vehicle theft. This has prompted the writer to conduct a research that aims to find out how to optimize the four-wheel patroli of the Samapta Unit in order to prevent the crime of theft. motorized vehicles in the jurisdiction of the Sragen Police. In this study, concepts and theories that are related to this research are used, including the concept of effort, the concept of patrolling, the concept of the Samapta Unit, the concept of motor vehicle theft, the theory of management elements, the theory of management functions, and the theory of SWOT analysis. The approach used in this research is a qualitative research approach with field research methods. Sources of data obtained in this study consisted of primary data sources, in the form of interviews conducted with several sources, and secondary data sources obtained from documents and books related to this research with data collection techniques obtained from interviews, observations. , as well as document studies. The data analysis technique used by the author in making this final project is in the form of data reduction, data presentation, and drawing conclusions. In this study it was found that the patroli carried out by the Samapta Polres Sragen Unit had been carried out in accordance with the expected conditions through three stages, namely the preparation stage, implementation stage, and termination stage. The influencing factors are classified into internal factors and external factors with internal factors consisting of supporting and inhibiting and external factors consisting of supporting and inhibiting. So we got some problem solving that can be done by conducting training for patroli officers, re-determining patroli routes, equipping patroli officers with sufficient equipment and weapons, equipping patroli vehicles with GPS, and establishing good relations with community leaders.